(untitled) (Research, Society and Development, 2023)
This study analyzed the healing and local anti-inflammatory activity of compounds from the aqueous extract of leaves of the plant Leonurus sibiricus L. (rubim) by evaluating the resolution of cutaneous wounds made in Wistar rats. The wounds were treated daily with the extract of L. sibiricus 10% (m/v) in sodium alginate 5% (m/v) to obtain a gel that facilitated its application; sodium alginate 5% (m/v) and Dexpanthenol 42 mg/g were used as negative and positive controls, respectively. The wounds were evaluated daily for appearance (crusting, swelling) and reduction during 21 days. The data were statistically analyzed and the results indicated that the extract of L. sibiricus favored a better healing evolution of the wounds when compared to the positive control, besides presenting less inflammatory exudate. Regarding the time of resolution (closure) of the wounds, no significant difference was observed between the animals treated with the extract of L. sibiricus and the negative control, however, the extract of L. sibiricus favored a more homogeneous healing giving the wound a better visual appearance, which was confirmed by microscopic analysis. These results corroborate the common sense knowledge of the population that uses this plant in relation to the indicated therapy.